Brief communication: The global signature of post-1900 land ice wastage on vertical land motion - R. E. M. Riva; T. Frederikse; M. A. King; B. Marzeion; M. R. van den Broeke (The Cryosphere, 2017)
Melting glaciers, ice caps and ice sheets have made an important contribution to sea-level rise through the last century. Self-attraction and loading effects driven by shrinking ice masses cause a spatially varying redistribution of ocean waters that affects reconstructions of past sea level from sparse observations. We model the solid-earth response to ice mass changes and find significant vertical deformation signals over large continental areas. We show how deformation rates have been strongly varying through the last century, which implies that they should be properly modelled before interpreting and extrapolating recent observations of vertical land motion and sea-level change.